2012
DOI: 10.1142/s0192415x12500450
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Total Flavonoids fromLitsea coreanaon Alcoholic Fatty Liver in Rats Associated with Down-Regulation Adipose Differentiation-Related Protein Expression

Abstract: Alcoholic fatty liver (AFL) is a reversible condition, but it can potentiate the development of alcoholic hepatitis and even cirrhosis by increasing oxidant generation, which is one of the key pathogenic factors and could result in alcoholic liver disease (ALD). Total flavonoids from Litsea coreana (TFLC), an active component extracted from Litsea coreana leve, have been shown to have therapeutic effects on hyperlipidemia. The present study was to evaluate the protective effects of TFLC on alcoholic fatty live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…In the current study, the identified compounds in GLE belong to different classes of natural products, e.g., anthocyanins, phenolic acids and derivatives, flavonoids, stilbenoids, and organic acids. Flavonoids were previously reported to exert a protective effect against alcohol-induced liver damage [57][58][59]. Anthocyanins, as a subclass of flavonoids, were previously found to play a role in the prevention of oxidative damage in living systems.…”
Section: (A)mentioning
confidence: 99%
“…In the current study, the identified compounds in GLE belong to different classes of natural products, e.g., anthocyanins, phenolic acids and derivatives, flavonoids, stilbenoids, and organic acids. Flavonoids were previously reported to exert a protective effect against alcohol-induced liver damage [57][58][59]. Anthocyanins, as a subclass of flavonoids, were previously found to play a role in the prevention of oxidative damage in living systems.…”
Section: (A)mentioning
confidence: 99%
“…Moreover, TFLC showed a protective effect on alcoholic fatty liver in rats. In an alcoholic fatty liver rat model, treatment with 200 mg/kg TFLC reduced the serum levels of triglycerides, total cholesterol, low-density lipoprotein (LDL)-cholesterol, TNF-a, glucose and insulin, and down-regulated the expression of hepatic adipose differentiation-related protein (Hu et al 2012). TFLC (100 mg/L) also reduced the activities of ALT and AST and the level of triglycerides in steatotic hepatocytes, and decreased the mRNA expressions of adipose differentiationrelated protein and peroxisome proliferator-activated receptor c (PPARc) (Hu et al 2013).…”
Section: Hepatoprotective Activitymentioning
confidence: 99%
“…Among these, the total flavonoids in Stellera chamaejasme L. (TFSC) and its derivatives with its unique physical and properties has been research hotspot of the world since 1980s, and has made big progress in medicine, food and chemical industry, environmental protection, agriculture and many other fields [ 19 , 20 ]. Recent studies have shown that treatment with flavonoids also benefits patients with NASH and NAFLD [ 21 ], However, the mechanisms responsible for lipid-lowering actions of total flavonoids in Stellera chamaejasme L. (TFSC) on liver remains unclear. In this study, we explored the efficacy of the different doses of TFSC supplements treatment on the HFD-induced hepatic steatosis and hyperlipidemia in rats.…”
Section: Discussionmentioning
confidence: 99%